Diversity of the egg tertiary membranes in some elasmobranch species and comments on the actual yolk-sac viviparous reproductive mode (Revista de Biología Marina y Oceanografía, 2022)
After fertilization, elasmobranch eggs (mostly megalecithal) are encapsulated in a tertiary membrane of different complexity, in the oviducal gland. The gross morphological characteristics of this membrane in elasmobranchs are highly variable, attaining it most sophisticates’ forms within the oviparous species. The purpose of this study was to contribute to the knowledge of the elasmobranch tertiary membranes, in both viviparous and oviparous species, and to discuss the relation with their role in protecting the embryos their development. In addition, the limitations of yolk-sac viviparity as a single reproductive mode category are commented, suggesting a new arrangement of taxa within that reproductive mode and new terminology. Data on tertiary membranes in elasmobranchs come from a large number of sources ranging from 1977 to date. Specimens were captured on board of commercial and scientific research cruises, from the following some major geographic regions: South Western Atlantic, South Western Pacific, and different areas of the Mediterranean Sea. In all, our records of tertiary membranes belong to ten species of sharks of five orders; Hexanchiformes, Squatiniformes, Heterodontiformes, Lamniformes, Carcharhiniformes, and eight species of rays and skates, of four orders: Rajiformes, Rhinopristiformes, Torpediniformes and Myliobatiformes. The reproductive modes reported for all this species were both lecithotrophic (yolk-sac viviparity, short single oviparity) and matrotrophic (ovotrophy, placentotrophy, limited and lipidic histotrophy). Six morphological and structural major patterns were detected within the yolk-sac viviparous species (type I to VI); a thin, diaphanous, shapeless membrane; candle capsules; oviparous-like tough egg capsule, and cases where no tertiary membrane was present.